Electronic Health Records in Arab Hospitals: A Systematic Review of Their Impact on Quality and Efficiency (2015–2024) - M Alotaibi, Muhammad Obaid; M Almohaimeed, Bader Rasheed; I Aljamaan, Abdulrahman Abdullah (Journal of Neonatal Surgery, 2025)
This systematic review explores the implementation and impact of Electronic Health Records (EHRs) in Arab hospitals over the last decade. The aim is to assess the extent to which EHR adoption has influenced healthcare quality and operational efficiency. Literature from databases including PubMed, Scopus, ScienceDirect, and Google Scholar was reviewed using the PRISMA methodology. A total of 47 peer-reviewed studies were included. Findings suggest that EHR implementation enhanced clinical documentation, reduced medication errors, and improved communication between healthcare providers. However, barriers such as lack of user training, resistance to technological change, infrastructure limitations, and fragmented health systems continue to pose significant challenges. Recommendations emphasize capacity-building, regional collaboration, Arabic-language system interfaces, and stronger regulatory frameworks.